Bangladesh agriculture in the 21st century - Faruqee, Rashid, 1938- (Dhaka, Bangladesh : University Press Ltd., 1998)
Outcome of an international conference sponsored by World Bank in 1995 in Dhaka.
Includes bibliographical references and index.
Keywords: Agriculture -- Economic aspects -- Bangladesh -- Congresses; Land use, Rural -- Bangladesh -- Congresses; Economics